The Site Selection Criteria for Designing the Essential Science Techno Park: in Trenggalek Regency - Petrisia, Alvania Valen; Rolalisasi, Andarita; Prakasa, Darmansjah Tjahja (Jurnal Lingkungan Karya Arsitektur, 2024)
Abstract: Trenggalek Regency is an area in the south of East Java province with a variety of potential in natural resources in the field of essential plants. Therefore, the government is trying to support the use and development in the Essentials sector by including the development of the Bendungan Trenggalek District Area as an Agricultural Technology Park and Essentials Science Techno Park area in the RPJMD (Regional Medium Term Development Plan) for Trenggalek Regency for 2021 - 2026 by carrying out Science Techno planning Park Atsiri. The planning for the Essential Science Techno Park is a form of effort to increase and support national research and improve the regional economy by carrying out research and development in the field of Essential Oils. The purpose of this research is to carry out landscape design and site analysis for educational tourism and the essential research center in Trenggalek Regency in order to realize a design that is in accordance with the vision and mission of the establishment of the Atsiri Science Techno Park. Selecting and arranging the right site also maximizes land use and creates buildings that stand in strategic and appropriate locations. Keywords: Science Techno Park; Essential; Site Analysis